Restoration of Przewalski's horse (Eqiudae, Perissodactyla) at the breeding centre of the Association «Wild Nature of Steppe», Russia - Victor A. Minoranskiy; Ali M. Uzdenov; Vasily I. Dankov; Yulia V. Malinovskaya (Nature Conservation Research: Заповедная наука, 2019)
The Association «Wild Nature of Steppe» located in Rostov Region (Russia) is engaged in the preservation of rare and valuable animals of the steppe zone. The Association breeding centre is located in a Protected Area, the Rostovsky State Nature Biosphere Reserve. The breeding centre of the Association «Wild Nature of Steppe» (size is 17.34 km2) is inhabited by the Bustard (Otis tarda), Bustling (Tetrax tetrax), Kulan (Equus hemionus kulan), Saiga (Saiga tatarica) and other animal species. The tarpan (Equus ferus ferus) lived on the European steppes until the 19th century. In 2013, the Association «Wild Nature of Steppe» transported four adult Przewalski's horses (Equus ferus przewalskii) from the F.E. Falz-Fein Biosphere Reserve «Askania-Nova» (Ukraine). The group consists of one male aged 5, two females aged 6 and one female aged 4 years. The article considers the aspects of transportation of the horses to Rostov Region, their acclimatisation and maintenance. The horses were initially placed in a quarantine pen. In 2014, they were transferred to an enclosure of 0.63 km2, in 2017 they were released into a larger enclosure of 5.12 km2. The article identifies the enclosures for the horses, their nutrition and behaviour. The animals produce offspring annually in the breeding centre of the Association «Wild Nature of Steppe». Currently, there are 14 Przewalski's horses in the breeding centre. This reflects rather favourable conditions for the animals. Three young males are kept separately from the main herd. A study on keeping the horses together with other animals: Kulan, Guanaco (Lama guanicoe), Père David's Deer (Elaphurus davidianus), Water buffalo (Bos bubalis), Domestic yak (Bos grunniens), American Bison (Bison bison) and others was conducted at the breeding centre. The Przewalski's horses successfully share the habitat with the Saiga and Bactrian camel (Camelus bactrianus). In the future it is planned to enlarge the horse enclosure and to bring some new specimens expanding the genetic diversity of the animal stock.